Penguatan 5 Pilar dalam Upaya Penurunan Stunting di Kelurahan Simokerto Kota Surabaya - Triannisa Wahyu Agitiya; Tiara Tivany (Universitas Batanghari Jambi, 2023)
The purpose of this study is to find out the five pillars in efforts to reduce stunting in Simokerto Village, Surabaya City. Research data collection using Focus Group Discussion (FGD). The targets of the EMAS Stunting Village Thematic KKN are brides-to-be, pregnant women, postpartum mothers and Baduta and toddlers. The results showed that there were 5 pillars of cultivation carried out by each